Improving opportunistic with social context communications - Quelhas, Rui Filipe Pedro (2011)
Opportunistic or Delay-tolerant Networks (DTNs) appeared as a promising concept towards what could be the future Internet. They pretend to overcome limitations faced by mobile environments with dynamic topologies, where the behavior of the network nodes leads to communication delay and disruptions. Following a rationale that undermines some wrong key assumptions made by traditional TCP/IP models, and considering them as features, not as exceptions, they introduce a novel message communication model, store-andforward, on which nodes store those messages as needed, forwarding them later, when contact opportunities arise. However, it still does not gather widespread acceptance, because it fits on different architectural proposals, not defining communication strategies adaptable to different scenarios nor proper support for the development of heterogeneous applications. This work builds on the concept of Pocket Switched Networks (PSNs)— an environment formed by nodes consisting of devices carried by persons— to propose the SociAL-based OppOrtunistic Networking (SALOON) framework, based on the Bundle Protocol and deployed on mobile computing systems, capable of promoting a convergence of the graph representing the physical encounters between those devices and an abstraction of the social graph of each user carrying it. It is intended to work as a testbed for the development of novel context-aware, particularly social-based, opportunistic routing protocols as well as to provide application support on top of a standard delaytolerant architecture. This framework aims to encourage the community to develop future research around opportunistic computing in a more uniform fashion.